2006
DOI: 10.1002/ijc.21961
|View full text |Cite
|
Sign up to set email alerts
|

Presence of high‐risk human papillomavirus DNA in penile carcinoma predicts favorable outcome in survival

Abstract: There is evidence that a subset of penile carcinomas is caused by infection with high-risk human papillomavirus (HPV). However, extensive studies on the possible influence of HPV infection on clinical outcome of penile cancer are lacking. This investigation is aimed to examine the prevalence of high-risk HPV in a large series of penile squamous-cell carcinomas (SCCs) and to determine the relationship between HPV and survival. Formalin-fixed, paraffinembedded tumor specimens of 171 patients with penile carcinom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
111
4
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 217 publications
(136 citation statements)
references
References 37 publications
12
111
4
2
Order By: Relevance
“…There was a significant frequency increase of HPV infection in penile cancer patients with age (p for trend 5 0.0122) this is consistent with the hypothesis that penile cancers develop by different etiologies and that HPV-positive tumor patients have a survival benefit as recently described by Lont et al 27 The nucleotide sequence analysis of 3 genomic regions (E6, E7 and LCR region) of 18 HPV16 isolates allowed the identification of European (E-G350) and non-European (Af1 and AA) variants. The percentage of penile carcinoma testing positive for non-European variants (55.6% of HPV16-positive samples) is much higher than that reported for cervical carcinoma in the same geographical area (33.3%).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…There was a significant frequency increase of HPV infection in penile cancer patients with age (p for trend 5 0.0122) this is consistent with the hypothesis that penile cancers develop by different etiologies and that HPV-positive tumor patients have a survival benefit as recently described by Lont et al 27 The nucleotide sequence analysis of 3 genomic regions (E6, E7 and LCR region) of 18 HPV16 isolates allowed the identification of European (E-G350) and non-European (Af1 and AA) variants. The percentage of penile carcinoma testing positive for non-European variants (55.6% of HPV16-positive samples) is much higher than that reported for cervical carcinoma in the same geographical area (33.3%).…”
Section: Discussionsupporting
confidence: 89%
“…[15][16][17][18][19][20][21][22][23][24][25][26][27] HPV16 is the most prevalent type in penile carcinoma and cervical carcinoma worldwide, with exception of the study by Senba et al, which found HPV18 in 55.4% of the tumors from northern Thailand. 1,28 HPV16, however is also the most common viral genotype identified in normal and diseased mucosa of male and female anogenital tract.…”
mentioning
confidence: 99%
“…At present, there are no evidences indicating the use of HPV detection in order to decide to perform lymphadenectomies. Surprisingly, Lont et al, although failed to associate HPV status and lymph node metastasis, showed better specific-disease survival in patients with ECP associated with high risk virus (p = 0.03) (17). In order to avoid bias in our study, we only evaluated inguinal disease-free survival (IDFI), that did not show differences between HPV positive and negative groups (p = 0.45).…”
Section: Discussionmentioning
confidence: 93%
“…Contrary to cervical cancers, which appear to be almost exclusively (>90%) driven by HPV, only a proportion of penile, vulvar, anal, and oropharyngeal cancers appear to be HPV driven (9,10). Interestingly, despite the clear oncogenic effects of HPV infection, HPV positivity appears to confer a survival benefit, this is particularly true for HNSCC, and also appears to be for penile cancer, although as yet only limited data are available (11).…”
Section: Introductionmentioning
confidence: 99%